2021
DOI: 10.1007/s11356-021-12685-4
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and simulated evaluations of airborne contaminant exposure in a room with a modified localized laminar airflow system

Abstract: The traditional mixing ventilation is not an energy effective approach to remove indoor air pollutants, maintain breath zone air quality, and control the airborne transmission. This study investigated the potential of a localized laminar airflow ventilation system to alleviate human exposure to pollutants. Breathing thermal manikins with sitting posture and supine posture were used to simulate the human. N2O was used as the tracer gas to simulate the indoor pollutants emission. The contaminant exposure index (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Furthermore, tracer gas simulations are less complex, and no assumption or simplification are required for the modelling, thus it is easier to obtain reliable results. According to this, to simulate the exhaled virus droplet nuclei from the source manikin, breathing thermal manikins [ 49 ] are needed, while the tracer gas concentrations could be monitored and measured via a set of fast gas concentration meters [ 50 ] to evaluate the exposure risk indices ( and IF) [ 51 , 52 ].…”
Section: Background Overviewmentioning
confidence: 99%
“…Furthermore, tracer gas simulations are less complex, and no assumption or simplification are required for the modelling, thus it is easier to obtain reliable results. According to this, to simulate the exhaled virus droplet nuclei from the source manikin, breathing thermal manikins [ 49 ] are needed, while the tracer gas concentrations could be monitored and measured via a set of fast gas concentration meters [ 50 ] to evaluate the exposure risk indices ( and IF) [ 51 , 52 ].…”
Section: Background Overviewmentioning
confidence: 99%
“…A comparison was made between the ophthalmologist's inhalation exposure in this study and the interpersonal exposure that has been reported in previous studies. As shown in Figure 3, the previous studies were classified as CFD (17)(18)(19)(20)(21)(22) or experimental studies, where the latter used tracer gas (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) or particles (34) to simulate droplets or droplet nuclei. In addition, Ueki (35) compared the inhalation exposure to live SARS-CoV-2 particles when wearing no mask, a surgical mask or an N95 respirator.…”
Section: Comparison Of Exposure In Typical Ophthalmic Proceduresmentioning
confidence: 99%
“…Thus, the most effective way to mitigate the pathogenic aerosols and other bio-contaminants in buildings is to provide an appropriate method of space ventilation. 3,16,17 Raymond Tellier 18 found that supply of the clean outdoor air (OA) dilutes indoor aerosol density quickly, and Jiang et al 19 and Bartlett et al 20 investigated the control of appropriate air change rate (air change per hour, ACH) and flow velocity and direction of the supply air, which are important to reduce infection risk in all building types (e.g. office, stores and public restaurants).
Figure 1.Simulation of indoor airflow and expiration in a building space.
…”
Section: Introductionmentioning
confidence: 99%